2014
DOI: 10.1021/ja500247b
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Copper Iodide Clusters: Insights into the Mechanochromic Luminescence Properties

Abstract: An in-depth study of mechanochromic and thermochromic luminescent copper iodide clusters exhibiting structural polymorphism is reported and gives new insights into the origin of the mechanochromic luminescence properties. The two different crystalline polymorphs exhibit distinct luminescence properties with one being green emissive and the other one being yellow emissive. Upon mechanical grinding, only one of the polymorphs exhibits great modification of its emission from green to yellow. Interestingly, the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
218
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(229 citation statements)
references
References 87 publications
10
218
0
Order By: Relevance
“…X ray diffraction studies revealed that the guest solvents, despite not having interaction with the host framework, do modulate the molecular packing and stacking in different ways that translates into the varied influences on Cu···Cu interactions through the outer organic ligand shell. Perruchas et al reported a cubane Cu(I) cluster showing mechano, thermo and vapochromic luminescent behavior [89]. [Cu 4 I 4 (PPh 2 (CH 2 ) 2 (CH 3 ) 2 SiOSi(CH 3 ) 2 (CH 2 ) 2 PPh 2 ) 2 ], 100, presents two A c c e p t e d M a n u s c r i p t Edited Mar 5 39 different crystalline polymorphs which exhibit distinct luminescence properties with one being green emissive 100a (λ em = 522 nm) and the other one being yellow emissive 100b (λ em = 571 nm) at room temperature ( Figure 19).…”
Section: -(4-pyridyl)tetrazole) (4-pt)mentioning
confidence: 99%
“…X ray diffraction studies revealed that the guest solvents, despite not having interaction with the host framework, do modulate the molecular packing and stacking in different ways that translates into the varied influences on Cu···Cu interactions through the outer organic ligand shell. Perruchas et al reported a cubane Cu(I) cluster showing mechano, thermo and vapochromic luminescent behavior [89]. [Cu 4 I 4 (PPh 2 (CH 2 ) 2 (CH 3 ) 2 SiOSi(CH 3 ) 2 (CH 2 ) 2 PPh 2 ) 2 ], 100, presents two A c c e p t e d M a n u s c r i p t Edited Mar 5 39 different crystalline polymorphs which exhibit distinct luminescence properties with one being green emissive 100a (λ em = 522 nm) and the other one being yellow emissive 100b (λ em = 571 nm) at room temperature ( Figure 19).…”
Section: -(4-pyridyl)tetrazole) (4-pt)mentioning
confidence: 99%
“…Surprisingly, the maximum uorescence emission wavelength exhibited a large blue shi when compared with NB-CQDs in aqueous solution, which may be attributed to the alteration of average NB-CQDs/ NB-CQDs distance. 27,28 The compactness of the NB-CQDs/PVA lm induced the interaction between these NB-CQDs, thus increasing the average NB-CQDs/NB-CQDs distance, resulting into the blue shi in the uorescence emission. 28 …”
Section: Anti-counterfeiting Of Nb-cqdsmentioning
confidence: 99%
“…During last few years, metal–organic hybrid materials (such as coordination polymers, metal–organic frameworks and complexes) with mechanochromism have also been increasingly investigated. According to the mechanisms, metal–organic mechanochromic materials can be divided into two types: (1) most of as‐reported systems are metal‐centered phosphorescence emission based on altering the arrangement of metals or clusters under the mechanical stimulus, such as Au I ,4 Pt II ,5 Cu I ,6 and Ir III ,7 etc. ; (2) the others involve fluorescence emission based on the change of the stacking mode and interaction of ligands, such as ligand‐based Zn II 8 and Cd II 9…”
mentioning
confidence: 99%